Penerapan Metode Newton Raphson untuk Pencarian Akar pada Fungsi Kompleks - Mohamad Syafii; Rahmi Ridhallah; Rizki Amalia Nur (JOSTECH Journal of Science and Technology, 2023)
This study aims to compare analytical methods and numerical methods in determining the roots of equations of a complex function. The numerical method used in this research is the Newton Raphson method. In this study two examples of complex functions were given, after which the roots of the equation were searched using the analytical method and the Newton Raphson method, then the results were compared. In this study, two examples are given, namely and . In example one, three different roots were obtained analytically, while numerical calculations using the Newton Raphson method obtained a value that converged to one of the roots that had been obtained analytically. In example two, four different roots were obtained analytically, while numerically using the Newton Raphson method similarly if done using the Newton Raphson method, a value that converged to one of the roots that had been obtained analytically was obtained.